The Use of Flipped Learning with Technology Integration to Improve Students’ Speaking Skills at MA Al-Ilham NW Selusuh - Raodatul Hikmah; Karyawan Putraidi; Ahmad Syukron Sidik (Tirai Edukasi : Jurnal Pendidikan, 2026)
This Study Investigates The Effectiveness Of A Flipped Learning Model Integrated With Technology In Improving Students’ Speaking Skills At MA Al-Ilham NW Selusuh. Employing A Quantitative Experimental Design With A One-Group Pre-Test And Post-Test, The Research Involved 20 Tenth-Grade Students Across Six Learning Sessions. Students Accessed Instructional Videos Outside The Classroom And Participated In Speaking Activities During Class Sessions. Data Were Collected Using Multiple-Choice Tests And Questionnaires. Results Revealed Significant Improvement In Students’ Speaking Ability, With Mean Scores Increasing From 44.75 (Pre-Test) To 73.50 (Post-Test). A Paired Sample T-Test Confirmed The Significance Of The Improvement (T = -14.750, P < 0.001). Questionnaire Analysis Indicated Positive Perceptions Of Flipped Learning And Technology Integration, Including Enhanced Motivation, Confidence, And Classroom Participation. The Findings Demonstrate That Flipped Learning, When Supported By Technology, Is An Effective Pedagogical Approach To Fostering Students’ Speaking Competence And Can Be Considered An Innovative Strategy For English Language Teaching In Indonesian Secondary Schools.